Prostate-specific antigen measured 3 months after radical prostatectomy as a new predictor of biochemical recurrence - Inoue, Hitoshi; Nishimura, Kensaku; Yamaguchi, Seiji; Nonomura, Norio; Hara, Tsuneo (International journal of clinical oncology, 2015)
Background This study was undertaken to investigate if the prostate-specific antigen (PSA) level measured 3 months after radical prostatectomy (RP) is a predictor of biochemical recurrence (BCR)-free survival. Methods We retrospectively reviewed the clinicopathologic data of 174 patients with a follow-up of at least 3 years after RP for clinically localized prostate cancer. None of the patients received neoadjuvant/adjuvant therapy. Subjects were categorized according to PSA level 3 months after RP (3M-PSA): <0.010 ng/mL (group 1; n = 119) or 0.010–0.100 ng/mL (group 2; n = 55). BCR was defined as two consecutive rises in PSA level ≥0.2 ng/mL. Results At a median follow-up of 69.5 months (range 36–113 months), 32 (18.4 %) patients experienced BCR. The median time to BCR was 16 months (range 4–98 months) after RP. The 5-year BCR-free survival rate was 92.6 and 57.4 % in groups 1 and 2, respectively. Patients in group 1 had a significantly higher BCR-free survival rate than those in group 2 (log-rank P < 0.001). According to the Cox proportional hazards model, patients with a 3M-PSA level of <0.010 ng/mL were at lower risk for BCR ( P < 0.001), along with pathologic Gleason sum 6 ( P = 0.028). PSA nadir level after RP was also a risk factor for BCR (log-rank P < 0.001). Area under the receiver operating characteristic curve for 3M-PSA to predict BCR was almost equivalent to that for the PSA nadir level (0.855 vs. 0.849). Conclusions 3M-PSA is an independent predictor of BCR-free survival. Our findings might be used for a risk-adjusted follow-up protocol.